2020
DOI: 10.1002/eat.23382
|View full text |Cite
|
Sign up to set email alerts
|

Eating disorder fear networks: Identification of central eating disorder fears

Abstract: Objective: Eating-related fear and anxiety are hallmark symptoms of eating disorders (EDs). However, it is still unclear which fears are most important (e.g., food, weight gain), which has practical implications, given treatments for eating-related fear necessitate modifications based on the specific fear driving ED pathology. For example, exposure treatments should be optimized based on specific fears that maintain pathology. The current study (N = 1,622 combined clinical ED and undergraduate sample) begins t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 57 publications
3
47
1
Order By: Relevance
“…Indeed, three out of four studies (Brown et al., 2020; Elliott et al., 2020; Hilbert et al., 2020; Olatunji et al., 2018) identified a predictive role of the most central nodes on the treatment outcome. This result is consistent with the findings in a population of obese people, including individuals with BED, undergoing bariatric surgery (Monteleone et al., 2019b) and those in a mixed population composed of people with EDs and healthy peers (Levinson & Williams, 2020). Instead, more research is needed to clarify whether a high network connectivity at the end of treatment points to a treatment not sufficiently targeting the relationships between symptoms and, thus, may represent an index of vulnerability to relapse, or points to the result of a better understanding of the relationships between symptoms promoted by the treatment itself.…”
Section: Discussionsupporting
confidence: 90%
“…Indeed, three out of four studies (Brown et al., 2020; Elliott et al., 2020; Hilbert et al., 2020; Olatunji et al., 2018) identified a predictive role of the most central nodes on the treatment outcome. This result is consistent with the findings in a population of obese people, including individuals with BED, undergoing bariatric surgery (Monteleone et al., 2019b) and those in a mixed population composed of people with EDs and healthy peers (Levinson & Williams, 2020). Instead, more research is needed to clarify whether a high network connectivity at the end of treatment points to a treatment not sufficiently targeting the relationships between symptoms and, thus, may represent an index of vulnerability to relapse, or points to the result of a better understanding of the relationships between symptoms promoted by the treatment itself.…”
Section: Discussionsupporting
confidence: 90%
“…Concern over being judged was the most central symptom, which is aligned with diagnostic criteria for SAD suggesting that fear of negative evaluation is central to the maintenance of SAD [71] and considered as an important component among preadolescents in educational settings [72]. Similarly, the current finding was partially in line with previous studies [73,74] in which shape-related judgment and fear of judgment due to weight gain were one of the most central ED fears. Additionally, outside of network studies, concern over being judged and/or evaluated would be conceptualized as a cognitive vulnerability or risk factor for SAD [20,21,75,76].…”
Section: Central Sad Symptoms In the Ed-sad Networksupporting
confidence: 87%
“…The clinical impact of the FGW and its associated negative consequences in patients with AN are well-known, being directly associated with other ED symptoms [11,14]. Indeed, several studies have claimed that tailored behavioral interventions targeting the FGW in AN are effective in reducing other ED symptoms [10,[26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…This, a small degree of positive weight gain activates a series of catastrophic beliefs based on continuous and uncontrollable weight gain expectations, which in turn lead to an exponential increase in FGW levels [10]. A recent study using network analyses found that most ED symptoms/pathology can be explained not by the unique effect of gaining weight, but by the negative associated consequences that patients usually report [11]. Based on this last assumption, it has been proposed that the extinction of the FGW in AN does not solely occur via a progressive habituation process towards weight recovery, but also via mechanisms of the inhibitory learning systems [10].…”
Section: Introductionmentioning
confidence: 99%